Influence of Baseline Magnetic Resonance Imaging Features on Outcome of Arthroscopic Meniscectomy and Physical Therapy Treatment of Meniscal Tears in Osteoarthritis. Issue 3 (March 2019) - MacFarlane, Lindsey A.; Yang, Heidi; Collins, Jamie E.; Guermazi, Ali; Jones, Morgan H.; Spindler, Kurt P.; Winter, Amelia R.; Losina, Elena; Katz, Jeffrey N.; ,; Brophy, Robert H.; Cole, Brian J.; et al.
Background: Arthroscopic partial meniscectomy (APM) is used to treat meniscal tears, although its efficacy is controversial. Purpose: This study used magnetic resonance imaging (MRI) to determine characteristics that lead to greater benefit from APM and physical therapy (PT) than from PT alone among patients with meniscal tear and knee osteoarthritis. Study Design: Cohort study; Level of evidence, 2. Methods: Using data from the Meniscal Tear in Osteoarthritis Research (MeTeOR) trial, the authors first assessed whether the effect of treatment on pain scores at 6 months differed according to baseline MRI features (bone marrow lesions, cartilage and meniscal damage). Second, the authors summed MRI features associated with differential pain relief between APM and PT to create a "damage score, " which included bone marrow lesion number and cartilage damage size with possible values of 0 (least damage), 1 (moderate), and 2 (greatest). The authors used linear models to determine whether the association between damage score and pain relief at 6 months differed for APM versus PT. Results: The study included 220 participants: 13%, had the least damage; 52%, moderate; and 34%, greatest. Although treatment type did not significantly modify the association of damage score and change in pain ( P interaction = .13), those with the least damage and moderate damage had greater improvement with APM than with PT in Knee injury and Osteoarthritis Outcome Score pain subscale—by 15 and 7 points, respectively. Those with the greatest damage had a similar improvement with APM and PT. Conclusion: Among patients with osteoarthritis and meniscal tear, those with less intra-articular damage on MRI may have greater improvement in pain with APM and PT than with PT alone. However, these results should be interpreted cautiously owing to the limited sample size.